Quilombo Mulher: as vozes das Anguta de Turi Vimba em documentos sonoros do Projeto Cafundó - Oliveira, Andreia Aparecida de (Universidade Federal de São Carlos, 2023)
This study aims to investigate the role of women in the formation of the Cafundó Quilombo Community, a rural area in the municipality of Salto de Pirapora, São Paulo, through the Matriarchs Dona Ifigênia Maria das Dores, Dona Benedita Pires Pedroso, and Cida Aguiar. To do so, I seek to analyze the life trajectories of these Anguta women, considering the territory as sacred land for the political bodies of black women, their ways of being, belonging, knowledge, and ancestral marks in this Quilombo Mulher. In this sense, I aim to understand their cultural references and the influences of their sociocultural and symbolic universe on the present territory. I highlight the protagonism of the matriarchs, who are responsible for preserving the lands, which have now been returned to the community, and for preserving the language spoken by them, Cupópia, a unique language developed by the group that combines African words such as Kimbundu, Umbundu, and Portuguese caipira, thereby passing down the memory of Turi Vimba to current generations. From a theoretical and methodological perspective, this is a bibliographical and documentary research using selected sound archives and newspaper articles, grounded in the works of Carlos Vogt and Peter Fry (VOGT; FRY, 2013), Lélia Gonzales (GONZALES, 2020), Beatriz Nascimento (RATTS, 2006), and Glória Moura (MOURA, 2012). The results point towards the recovery of ancestry and the memories of the matriarchs in recording the history of the Cafundó Quilombo, reconstructing a part of this past that still resonates in current generations.
Quilombo woman: women's voices by Turi Vimba in sound documents from the Cafundó Project
Keywords: Ancestralidade; Mulher Negra; Quilombo; Memórias; Ancestry; Black Women; Quilombo; Memories; CIENCIAS HUMANAS